Theology, Witness, and Spirituality in a Post-Secularized Historical Context - Voulgaraki-Pissina, Evi (Religions, 2023)
Religion and spirituality are seen to be making a comeback since the 1990s and increasingly thereafter in the European context. However, traditional forms of Christianity are diminishing, while other types of religion take the lead. An increasing number of voices are being raised among Christians, calling for a re-evangelization of society. Nevertheless, there is some skepticism about such activism against the backdrop of plurality, human rights, and freedom, regarding not only issues of political correctness but also considering the question of efficacy. While spirituality abounds, even among conscientious Orthodox Christians, there is still a need for theology. Even among Orthodox Christians, spirituality is mainly linked with a withdrawal from the world, history, and the political, often taking a ritualistic character expressed in religious acts of pietism through habits and customs. This is unfair to the historical and liberating physiognomy of the Orthodox Christian faith, as it does not differ much from other types of new age religious movements. In order to foster Christian witness amidst the desert of post-modern cities, one must rediscover theology. Theology, centered around the Gospel and the patristic tradition, can contribute vital missing elements and does justice to the Incarnation of pre-eternal Logos, to the Resurrection, and to the fulfillment of life. Unless Christians grow in their understanding of theology and the world around us, there will be only mirages of spirituality that take the place of a spirituality derived from faith and its incisiveness and meaningfulness for life today.